2021
DOI: 10.3390/nano11123219
|View full text |Cite
|
Sign up to set email alerts
|

Nanoantennas Inversely Designed to Couple Free Space and a Metal–Insulator–Metal Waveguide

Abstract: The metal–insulator–metal (MIM) waveguide, which can directly couple free space photons, acts as an important interface between conventional optics and subwavelength photoelectrons. The reason for the difficulty of this optical coupling is the mismatch between the large wave vector of the MIM plasmon mode and photons. With the increase in the wave vector, there is an increase in the field and Ohmic losses of the metal layer, and the strength of the MIM mode decreases accordingly. To solve those problems, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…They concluded that the funneling areas of both sides were symmetric. Pardo et al [ 5 ] explained light funneling of an oblique incident light as a consequence of magnetoelectric interference (MEI) [ 4 , 44 , 45 , 46 ] effect. They considered an optimized device at the resonance wavelength so that no wave was reflected and the funnel widths of both sides were almost symmetrical even at large incident angles, such as 30° and 50°.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the funneling areas of both sides were symmetric. Pardo et al [ 5 ] explained light funneling of an oblique incident light as a consequence of magnetoelectric interference (MEI) [ 4 , 44 , 45 , 46 ] effect. They considered an optimized device at the resonance wavelength so that no wave was reflected and the funnel widths of both sides were almost symmetrical even at large incident angles, such as 30° and 50°.…”
Section: Introductionmentioning
confidence: 99%